İbn Haldun ile John Locke’un Epistemoloji ile ilgili Bazı Görüşlerinin Karşılaştırılması - Hacer Âşık EV (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this article some opinions of Ibn Haldun who lived at the end of the Middle Age and some opinions of John Locke who lived in the New Age about epistemology were tried to be compared from some aspects. For both thinkers, who have rejected the innatism and accepted the mind as a blank slate at first, the source of knowledge is senses and thought. According to Ibn Haldun, the knowledge’s subject is universals, and according to Locke, the knowledge’s subject is ideas and the relations between ideas. Ibn Haldun asserted that the perceptions about concretes are more reliable and far from fault than abstracts. Locke accepted that the intuitive knowledge is the most evident and reliable knowledge